Assessing the Effectiveness of Goods and Service Tax Collection in Palu’s Food and Beverage Sector - Rudin M.; Maria Lea Frensy Bakarbessy (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Regional revenue from Certain Goods and Services Tax (PBJT) plays a crucial role in supporting development financing, particularly in productive sectors such as food and beverages. This study aims to examine and analyze the effectiveness of PBJT collection in the food and beverage sector in Palu City. A quantitative research approach was used, relying on secondary data from 2020 to 2024, including annual PBJT revenue targets and actual realization figures specifically for the food and beverage industry. This analysis revealed three main findings. First, PBJT collection was categorized as very effective in 2020, 2021, and 2022, but became ineffective in 2023 and 2024. Second, the effectiveness of tax collection in the early years was supported by a conducive investment climate in Palu City, which helped increase regional revenue, particularly from the food and beverage sector. Third, the main obstacles to effective tax collection include the limited number and capacity of human resources in the regional tax authority, as well as low public awareness and use of the PBJT online payment system. These findings indicate the need to improve administrative capacity and digital literacy to improve tax compliance and regional revenue performance in the future.